Aromaterapi Lavender melalui Humidifier terhadap Kualitas Tidur Pasien Kanker Payudara - Sediana Sagala; Dudut Tanjung; Elmeida Effendy (Jurnal Keperawatan Silampari, 2022)
This study aims to identify the effect of lavender aromatherapy intervention on the sleep quality of breast cancer patients. The research method used is quantitative with a randomized controlled trial design with a control group pretest-posttest design. The results showed a difference in the mean sleep quality in the intervention group and the control group after being given the intervention with a p-value of 0.005 (p < 0.05). In conclusion, lavender aromatherapy is recommended as an alternative therapy to improve the sleep quality of breast cancer patients. Keywords: Lavender Aromatherapy, Breast Cancer, Sleep Quality